INDIVIDUAL BEHAVIOR MEASUREMENT MODEL: INDIVIDUAL CHARACTERISTICS, WORK CULTURE AND WORKLOAD (LITERATURE REVIEW MSDM) - Rajab, Muhammad (Dinasti Publisher, 2021)
The role of previous research or relevant research is very important and useful, because it can help and function to strengthen theoretical studies and phenomena of the relationship or influence between variables in a study. This article reviews and seeks to confirm the factors that influence individual behavior and organizational citizenship behavior which include individual character, work culture and workload. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. Human Resource Management literature study results from library research are that: 1) individual characteristics affect individual behavior; 2) work culture influences individual behavior; 3) workload affects individual behavior;